Implementation of child development evaluation at the Aisyiyah Nambangan Selogiri Pre-school, Wonogiri Regency - Rahayu, Titik; Darsinah, Darsinah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to describe the implementation of child devel-opment evaluation at PAUD Aisyiyah Nambangan Selogiri, Wonogiri Regency. Methodology: This study is a Qualitative Descriptive study. Data sourceit is from teachers of Group A and B. Data were obtained through observation, interviews, and documentation. Data validation used triangulation techniques. Data analysis techniques used Miles and Huberman analysis by collecting data, reducing data, presenting data and drawing conclusions. Results: The results of the study showed that the implementation of development evaluation at PAUD Aisyiyah (1) Daily evaluation implementation was car-ried out every day, according to learning objectives and notes in checklist format in the objectives column (KD). (2) Weekly evaluations are not carried out, but daily evaluations are summarized, namely the accumulation of daily evaluations and will be repeated if the child's development has not been achieved., by summarizing the daily evaluation based on the learning objec-tives that have not been achieved by the child, so that the teacher can take the results of the evaluation and repeat the learning objectives that have not been achieved by the child. (3) Implementation of semester evaluations is carried out by taking summarized daily evaluations and data. collectedAfter that, the evaluation is made into a Child Development Report which will later be reported to parents at the end of the semester. Applications/Originality/Value: In implementing development evaluations, feedback is needed for teachers that can be used to improve the teaching and learning process and the eval-uation process.